A Review of Constructal Design of Heat Exchangers - Salih, Salemaa Rashid; Mustafa, Ahmed Waheed; Awad, M. M. (Al-Nahrain Journal for Engineering Sciences, 2025)
A substantial amount of research has been dedicated to improving the efficiency of heat exchangers, which are extensively utilized in electronic equipment, heating and air conditioning systems, space vehicles, thermal power systems, industrial applications, and transportation. Enhancing the efficiency of these devices can lead to significant reductions in materials, cost, and space. Constructal design offers a promising approach to optimizing various heat transfer systems, including electronic packages, by applying the constructal law to achieve optimal configurations. This review aims to examine recent advancements in the application of constructal design theory to heat exchangers and its potential for enhancing thermal performance. The most recent state-of-the-art developments are thoroughly described, along with their evaluating parameters, and recommendations for further research in this field are provided.